2021
DOI: 10.1007/s12028-020-01180-2
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral Hemorrhage with Intraventricular Extension Associated with Loss of Consciousness at Symptom Onset

Abstract: Background In patients with spontaneous intracerebral hemorrhage (ICH), pre-hospital markers of disease severity might be useful to potentially triage patients to undergo early interventions. Objective Here, we tested whether loss of consciousness (LOC) at the onset of ICH is associated with intraventricular hemorrhage (IVH) on brain computed tomography (CT). Methods Among 3000 ICH cases from ERICH (Ethnic/Racial Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…We have chosen to dichotomize our data to remain consistent with recent ICH studies, rendering mRS score 0-3 as favorable. 11,23,30 Recognizing, however, the significant heterogeneity native to mRS score 3, we have reported mRS score 3 independently (Tables 2 and 4) as perhaps an indeterminate outcome.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We have chosen to dichotomize our data to remain consistent with recent ICH studies, rendering mRS score 0-3 as favorable. 11,23,30 Recognizing, however, the significant heterogeneity native to mRS score 3, we have reported mRS score 3 independently (Tables 2 and 4) as perhaps an indeterminate outcome.…”
Section: Discussionmentioning
confidence: 78%
“…22 Favorable and unfavorable functional outcomes were defined as an mRS score of 0-3 and 4-6, respectively. 11,23,24 Based on the review of all pertinent clinical records of the entire cohort, radiologic images, and autopsy reports (when available), cause-specific mortality was categorized into neurologic vs medical. Primary pathophysiologic mechanisms leading to death or decision to withdraw lifesustaining therapy were categorized by adjudication.…”
Section: Surgical and Medical Carementioning
confidence: 99%
“…IVH is predictive of early (within 24 h) and late (up to 7 days) neurological deterioration [ 86 ] and poor outcome [ 87 , 88 ]. IVH is also strongly associated with pre-hospital loss of consciousness [ 89 ]. It has been shown that the prognostic value of hematoma expansion is even higher if the IVH component is also included [ 90 ].…”
Section: Neuroimaging Of Ichmentioning
confidence: 99%
“…APACHE score [26,60] Serum hemoglobin [61] Serum neutrophil to lymphocyte ratio [62,63] Cerebral perfusion pressure and partial pressure of oxygen in interstitial brain tissue (PbtO2) [64] Serum iron/ferritin/transferrin [65] Chronic kidney disease [66] Imaging Variables IVH expansion [50,51,67] Peak PHE [68] Spot sign/island sign/black hole sign/blend sign [69] Non contrast CT-Hypodensities on CT [69,70]…”
Section: Physiologic Variablesmentioning
confidence: 99%